Mobile Applications and Tourist Loyalty in Malaysia: A Comparative Case Study of Malaysia Airlines and AirAsia - Mohamed, Muhammad Kyrie Zariff; Mohd, Nur Shuhadah; Najimudin, Muhammad Fadhlullah (IIUM Press, 2025)
In today’s globalised world, mobile platforms have become indispensable, especially in tourism, where travel applications enhance efficiency and convenience. Yet, despite their potential, airline mobile applications face persistent challenges such as low user engagement, limited utilisation, and minimal adoption for flight bookings. This study explores how the attributes of airline mobile applications influence tourist loyalty within the Malaysian context. Employing a quantitative approach, the research analyses patterns of tourist loyalty in relation to the use of airline mobile applications. The findings identify five key attributes shaping loyalty: user experience, usability, interface design, security features, and system compatibility. These characteristics show significant positive relationships with tourist loyalty, with some exerting stronger influence than others. The study offers important practical implications for airlines and tourism stakeholders by emphasising the strategic design of mobile applications that prioritise these attributes to strengthen customer retention. By optimising application features, airlines can enhance user engagement and increase the adoption of mobile bookings in the Malaysian market. This research also contributes to the literature on tourism and mobile technologies by providing empirical evidence on the direct impact of mobile application attributes on tourist loyalty in a developing aviation market. It highlights the need for well-designed, secure and user-friendly platforms to meet travellers’ expectations and sustain competitive advantage in an increasingly digitalised tourism environment.